Primitive tumors of the jejunum-ileum - Filgueira, José L; Facal, José (Cirugía del Uruguay, 2020)
With regard to personal observation, a review is made of the jejunum-ileum tumors treated at the Hospital de Clínicas up to the present time. Are analyzed its clinical, radiological and pathological aspects, the therapeutic guidelines used and the results obtained are considered.